Surfactant-assisted encapsulation of uniform SnO2 nanoparticles in graphene layers for high-performance Li-storage. (13th January 2015) - Ai, Wei; Zhu, Jianhui; Jiang, Jian; Chao, Dongliang; Wang, Yanlong; Fan Ng, Chin; Wang, Xiuli; Wu, Chao; Li, Changming; Shen, Zexiang; Huang, Wei; Yu, Ting
Abstract: SnO2 /graphene composite has been regarded as the alternative anode material for next generation high-performance lithium-ion batteries (LIBs). Here we report an efficient and facile one-pot strategy for the synthesis of SnO2 /graphene composite through a surfactant-assisted redox process. The presence of surfactant can provide homogeneous nucleation sites for SnO2 nanoparticles formation, thus ensuring the generated SnO2 nanoparticles have a tiny size of ∼5 nm and are uniformly distributed on the graphene sheets. Simultaneously, the random aggregation of graphene sheets leads to the in-situ encapsulation of SnO2 nanoparticles into graphene layers, forming a mechanically robust composite structure. These unique structural features are not only favorable for fast electrons transport and Li ions diffusion, but also capable of effectively buffering the volume changes of SnO2 nanoparticles. As a consequence, the SnO2 /graphene composite exhibits superior Li storage performance in terms of large reversible capacity, good cycling stability and excellent rate capability.